THE 29th MEETING OF THE FEDERAL INTERDEPARTMENTAL COORDINATIONAND METHODOLOGY COUNCIL ON FORENSIC SCIENCE AND FORENSIC EXAMINATIONS WAS HELD ON 24 DECEMBER, 2014 - O. Miklyaeva (Теория и практика судебной экспертизы)
.